Existence of Sobokartti Building as A Physical Culture in Semarang City in Law Anthropology Approach - Handayani, Emy; Wicaksono, Satrio Adi (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
Physical culture can be understood as objects created by human beings which are an embodiment of the growth and development of cultural values ​​in a particular society, in the form of buildings that have been designated as cultural heritage buildings in the city of Semarang. The building is the Semarang Sobokartti building on Jalan Dr. Cipto Semarang, which is a reflection of the development of humans to always preserve culture both Javanese culture and western or European culture The approach used in this research is an empirical approach and a comparative approach to law anthropology. In an empirical approach, the sobokartti building is a physical culture which is a historic building that accommodates traditional arts which are closely related to Javanese culture, namely karawitan training, puppetry routine, puppetry courses, host courses, dancing courses and batik training. It should be appreciated because the community can maintain its preservation until now by showing the existence of Javanese culture with a love for culture that deserves to be preserved and for the nation's successor generation. Likewise with a comparative approach, it is said that the existence of physical culture in the sobokartti building is expected by the government to have regulations on cultural heritage objects, namely historic buildings or ancient buildings of the Sobokartti Semarang building as outlined in the Cultural Heritage Law No. 11 of 2010 to protect cultural heritage buildings with the aim of preserving, utilizing, and maintaining the beauty of a cultural heritage building Sobokartti Semarang. Suggestions that will be used in this research that is the role of the Government and Society to maintain physical cultural wealth should be developed by the nation's next generation, with the utilization of the Sobokartti building can provide sustainable use. So that, the Government and the community have the desire to protect and preserve the function of the Sobokartti Semarang building.